2011
DOI: 10.1093/fampra/cmr034
|View full text |Cite
|
Sign up to set email alerts
|

Views of health professionals on the role of primary care in the follow-up of men with prostate cancer

Abstract: Background. Follow-up care for prostate cancer has traditionally been led by secondary care in hospital out-patient clinics. As the number of men with prostate cancer increases and secondary care resources face pressure, alternative follow-up models are being sought. Current National Institute for Health and Clinical Excellence guidance recommends follow-up outside the hospital setting for patients who are stable 2 years following radical treatment and for those undergoing 'watchful waiting'. Objective. To des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 12 publications
3
35
1
Order By: Relevance
“…Studies have shown willingness from PCPs and support from secondary care for increased primary care involvement in follow-up, provided that adequate guidelines, educational support (knowledge and skills), clear lines of communication with easy access back to secondary (hospital) care, robust monitoring systems in primary care, and adequate resourcing are available. 190,191 Patients recognise the potential benefi ts in terms of convenience, familiarity, and knowledge of comorbidities and family situation off ered by primary care, but they express concerns about PCPs having the level of knowledge needed. 191 Nevertheless, some patients gain considerable reassurance from followup care delivered in hospital settings.…”
Section: Models To Deliver Survivorship Carementioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown willingness from PCPs and support from secondary care for increased primary care involvement in follow-up, provided that adequate guidelines, educational support (knowledge and skills), clear lines of communication with easy access back to secondary (hospital) care, robust monitoring systems in primary care, and adequate resourcing are available. 190,191 Patients recognise the potential benefi ts in terms of convenience, familiarity, and knowledge of comorbidities and family situation off ered by primary care, but they express concerns about PCPs having the level of knowledge needed. 191 Nevertheless, some patients gain considerable reassurance from followup care delivered in hospital settings.…”
Section: Models To Deliver Survivorship Carementioning
confidence: 99%
“…190,191 Patients recognise the potential benefi ts in terms of convenience, familiarity, and knowledge of comorbidities and family situation off ered by primary care, but they express concerns about PCPs having the level of knowledge needed. 191 Nevertheless, some patients gain considerable reassurance from followup care delivered in hospital settings. It has been acknowledged that patients are not well informed about the evidence of limited benefi t for conventional follow-up schedules and that their preferences might change if the evidence was more widely understood.…”
Section: Models To Deliver Survivorship Carementioning
confidence: 99%
“…6 The specialists have a thorough knowledge of cancer and easier access to imaging and laboratory tests, but some of these tests are often unnecessary, and they only raise anxiety of patients, focusing on their illness and not on their wellness. 7 General gynecologists may play an intermediary role between the specialist and general practitioner.…”
Section: Who Makes a Follow-up? The Role Of Specialists And General Pmentioning
confidence: 99%
“…An effort should be done to promote better communication and cooperation between specialists and general practitioners for transferring follow-up care from hospital to the community. 7 Randomized clinical trials (RCTs) comparing the role of specialist and general practitioner in low stage breast cancer showed no difference in recurrence rate, death rate, and QoL, 8,9 but higher satisfaction in patients followed by their general practitioner. 10 Moreover breast cancer follow-up by the general practitioner was less costly than routine hospital follow-up, by a mean of U130 (179 €; 198 $) per patient.…”
Section: Who Makes a Follow-up? The Role Of Specialists And General Pmentioning
confidence: 99%
“…Studies have also shown that healthcare professionals involved in secondary (hospital-based) and primary (general practitioner (GP) clinic-based) care see a greater role for primary care in delivering follow-up care,13 and that this would be acceptable to men with prostate cancer 6. A recent literature review found no significant differences in patient outcomes in primary versus secondary care follow-up for breast and bowel cancer 14.…”
Section: Introductionmentioning
confidence: 99%